2014
DOI: 10.1111/jgh.12473
|View full text |Cite
|
Sign up to set email alerts
|

Presence of spur cells as a highly predictive factor of mortality in patients with cirrhosis

Abstract: The presence of spur-cell anemia is not uncommon in cirrhosis and seems to be strongly associated with mortality. SCA can be used in combination with MELD as an additional predictor of early mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 18 publications
0
31
1
Order By: Relevance
“…A prospective study by Alexopoulou et al indicated that in patients with liver cirrhosis and spur cell anaemia, higher mortality has been reported compared with cirrhotic without spur cell anaemia. The study which included 116 patients with cirrhosis reported survival rates of 77%, 45% and 33%, in patients with spur cell anaemia, at 1-month, 2-month and 3-month follow-up, respectively 18. As life span of these patients is short, the question of long-term toxicity of steroids may not be of overwhelming concern.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study by Alexopoulou et al indicated that in patients with liver cirrhosis and spur cell anaemia, higher mortality has been reported compared with cirrhotic without spur cell anaemia. The study which included 116 patients with cirrhosis reported survival rates of 77%, 45% and 33%, in patients with spur cell anaemia, at 1-month, 2-month and 3-month follow-up, respectively 18. As life span of these patients is short, the question of long-term toxicity of steroids may not be of overwhelming concern.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hemolytic anemia with acanthocytosis is a severe manifestation of advanced cirrhosis with a poor prognosis . Reduced erythrocyte lifespan in this situation results from both dysregulated membrane lipids and oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hemolytic anemia with acanthocytosis is a severe manifestation of advanced cirrhosis with a poor prognosis. 2 Reduced erythrocyte lifespan in this situation results from both dysregulated membrane lipids and oxidative damage. Thus, there is a rationale to administrate vitamin E in order to improve red blood cell membrane alterations and to reduce hemolysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations